Alpaca (Vicugna pacos) Skin Analyzed Under Architecture and Structure - Sasahara, Tais Harumi de Castro [UNESP]; Neira, Luciana Milagros Durand; Gomes, Silvio Pires; McManus, Concepta Margaret; Chiarello, Guilherme; Miglino, Maria Angelica (Soc Chilena Anatomia, 2024)
This study evaluated the morphology of alpacas skin. Biopsies were collected and samples were fixed in 10 % neutral buffered formalin for histological procedures. The sections were stained with hematoxylin and eosin, picrosirius red and Masson's trichrome. Types I, III and IV collagen were analyzed by immunohistochemistry. The derma presented sebaceous and sweat glands, as well as follicular groups with medullated fibers. Type I and type IV collagen were observed at epidermis and dermis as well as in glandular structures and hair follicles. The collagen III, was observed only in dermis.
Keywords: Histology; Integument; Immunohistochemistry; Scanning electron microscopy.